A conceptual analysis of the meaning of comfort at the end-of-life using the Walker and Avant (2014) Framework - Hou Yong-Chao; Timmins Fiona; Zhou Qian; Wang Ju-Zi (Sciendo, 2021)
The aim of the authors is to clarify the concept of comfort at the end-of-life in order to support understandings of fundamental nursing care needed at this stage of healthcare.